Our product is unique: A note on a delegation game with differentiated products - Clemens Buchen; Sven A. Hartmann; Alberto Palermo (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2021)
We analyze a Cournot duopoly market with differentiated goods and the separation between ownership and control. We consider a delegation game, for which the owner of a firm hires a manager who acts as if the good has a lower degree of substitutability than it really has. This is so either because managers are biased and perceive the good in this way, or because firms design an incentive scheme accordingly, which leads the manager to act in this way. Both firms rely on delegation. We discuss conditions, which lead one firm to increase its profit implying that the usual result of a prisoners' dilemma is avoided.
Keywords: D21; D62; L13; 330; Strategic Delegation; Managerial Incentives; Oligopoly